Heat-Treated Probiotics’ Role in Counteraction of Skin UVs-Induced Damage In Vitro - Giorgia Mondadori; Angela Amoruso; Annalisa Visciglia; Giovanni Deusebio; Daniela Pinto; Marco Pane; Fabio Rinaldi (Cosmetics)
Prolonged exposure to ultraviolet (UV) radiations represents a significant risk factor and may lead to various skin disorders, premature aging, and an increased susceptibility to skin cancers. Recently, probiotics have emerged as promising candidates for fortifying the skin’s natural defences through their diverse mechanisms. The aim of the present work was exploring the potential of five heat-treated probiotics (SkinbacTM, Probiotical Research S.r.l., Novara, Italy), as protective agents against UVA and UVB damages on human keratinocyte line (HaCaT) and human skin 3D model (Phenion® Full-Thickness Skin Model, Henkel AG & Co. KGaA, Dusseldorf, Germany). The protective role toward artificially induced oxidative stress was evaluated by determining the residual viability after UV exposure and analyzing gene expression of markers involved in apoptosis (Tumor protein 53), inflammation/immunosuppression (Interleukin 6), oxidative stress (oxidative stress response enzyme heme oxygenase 1), investigated using quantitative real-time PCR. Additionally, we examined the protective effects of these strains, testing them on Normal Human Epidermal Keratinocytes (NHEK) irradiated with UVC, specifically, evaluating the expression of tight junction proteins, including claudin 1, claudin 4, and occludin, by ELISA. The tested heat-treated probiotics effectively protected from UVA, UVB, and UVC damage on all end points analyzed, revealing their capacity to enhance barrier protection in cases of damage and their potential for innovative skincare strategies centered around probiotic-based formulations for enhanced protection against UV-induced skin damage.